Atp-Loaded Biomimetic Nanoparticles as Controlled Release System for Extracellular Drugs in Cancer Applications - Garcia Huidobro-Toro, J; Diaz-Saldivar, P (Dove Medical Press Ltd., 2019)
Purpose: The antitumoral effect of ATP requires its accumulation in the extracellular space to interact with membrane receptors in target cells. We propose the use of albumin nanoparticles (ANPs) coated with erythrocyte membranes (EMs) to load, deliver, release, and enhance the extracellular anticancer activity of ATP. Materials and methods: ANPs were synthesized by desolvation method and optimal values of pH, albumin concentration, and ethanol volume were determined. EMs were derived from erythrocyte lysates and were coated on to ANPs using an extruder. Size was determined by transmission electron microscopy (TEM) and hydrodynamic size and zeta potential were determined by dynamic light scattering. Coating of the ANPs with the EMs was verified by TEM and confocal microscopy. Nanoparticle cell uptake was analyzed by confocal microscopy using HeLa and HEK-293 cell cultures treated with nanoparticles stained with 1,1 -dioctadecyl- 3,3,3 ,3 - tetramethylindodicarbocyanine, 4-chlorobenzenesulfonate salt (DiD) for EM-ANPs and Alexa 488 for ANPs. Cell viability was analyzed by [3-(4,5-dimethylthiazol- 2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt (MTS) and Annexin V/propidium iodide assays. Results: Optimal values of ANP preparation were as follows: pH=9, 10 mg/mL albumin concentration, and 2.33±0.04 mL ethanol volume. Size distributions as analyzed by TEM were as follows: ANPs =91.9±4.3 nm and EM-ANPs =98.3±5.1 nm; hydrodynamic sizes: ANPs =180.5±6.8 nm and EM-ANPs =197.8±3.2 nm; and zeta potentials: ANPs =17.8±3.5 mV, ANPs+ATP =-13.60±0.48 and EM-ANPs =-13.7±2.9 mV. The EMs coating the ANPs were observed by TEM and confocal microscopy. A fewer number of internalized EM-ANPs+ATP compared to non-coated ANPs+ATP was observed in HeLa and HEK-293 cells. Cell viability decreased up to 48.6%±2.0% with a concentration of 400 µM ATP after 72 hours of treatment and cell death is caused mainly via apoptosis. Conclusion: Our current results show that it is possible to obtain nanoparticles from highly biocompatible, biodegradable materials and that their coating with EMs allows the regulation of the internalization process in order to promote extracellular activity of ATP. © 2019 Díaz-Saldívar and Huidobro-Toro.